Validation study of the leeds dyspepsia questionnaire in a multi-ethnic Asian population - Mahadeva, S.; Chan, W.K.; Mohazmi, M.; Sujarita, R.; Goh, K.L. (2011)
Background and Aim: Outcome measures for clinical trials in dyspepsia require an assessment of symptom response. There is a lack of validated instruments assessing dyspepsia symptoms in the Asian region. We aimed to translate and validate the Leeds Dyspepsia Questionnaire (LDQ) in a multi-ethnic Asian population. Methods: A Malay and culturally adapted English version of the LDQ were developed according to established protocols. Psychometric evaluation was performed by assessing the validity, internal consistency, test-retest reliability and responsiveness of the instruments in both primary and secondary care patients. Results: Between April and September 2010, both Malay (n = 166) and Malaysian English (n = 154) versions were assessed in primary and secondary care patients. Both language versions were found to be reliable (internal consistency was 0.80 and 0.74 (Cronbach's alpha) for Malay and English, respectively; spearman's correlation coefficient for test-retest reliability was 0.98 for both versions), valid (area under receiver operating curve for accuracy of diagnosing dyspepsia was 0.71 and 0.77 for Malay and English versions, respectively), discriminative (median LDQ score discriminated between primary and secondary care patients in Malay (11.0 vs 20.0, P < 0.0001) and English (10.0 vs 14.0, P = 0.001), and responsive (median LDQ score reduced after treatment in Malay (17.0 to 14.0, P = 0.08) and English (18.0 to 11.0, P = 0.008) to dyspepsia. Conclusions: The Malaysian versions of the LDQ are valid, reliable and responsive instruments for assessing symptoms in a multi-ethnic Asian population with dyspepsia.